Identification And Distribution Of Marine Dinoflagellates At Sebatu And Sungai Rambai, Malacca, Malaysia - Mohammad Noor, Normawaty (1998)

(untitled)
Phytoplan11on is an important organism in the aquatic ecosystem as a primary producer. However, some species of phytoplankton also causes red tides or harmful algal blooms (HAB) which lead to negative impacts on human health, economics, aquaculture, fisheries and tourism. In this study, dinoflagellates, the main causative organism of red tides, were identified and enumerated from samples taken at Sebatu and Sungai Rambai, Malacca. In the identification of dinoflagellates, thecal plate tabulation and morphological characters of the cells were observed by light and electron microscopy.Thirty four species of dinoflageRates were identified, which consists of 10 potential HAB species viz.